2013
DOI: 10.1074/jbc.m113.495069
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin E3 Ligase CRL4CDT2/DCAF2 as a Potential Chemotherapeutic Target for Ovarian Surface Epithelial Cancer

Abstract: Background: Cullin-RING ubiquitin ligases are the largest family of E3 ligases, but their roles in ovarian cancers remain uninvestigated. Results: Inhibition of CRL4 activity induced ovarian cancer death. Conclusion: CRL4CDT2 repression and CDT1 accumulation contributed to the genotoxic effects of MLN4924 in ovarian cancer cells. Significance: Indicating CRL4CDT2 is an effective drug target in ovarian cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 37 publications
2
76
0
Order By: Relevance
“…2F), suggesting that IP6K1 prevents c-Jun ubiquitylation and degradation. In line with this notion, MLN-4924, a NEDD8-activating enzyme inhibitor that reduces the neddylation and catalytic activity of CRL4 (31,32), dose-dependently increases levels of c-Jun in IP6K1-null, but not wild-type, MEFs (Fig. 2G).…”
Section: Ip6k1supporting
confidence: 66%
“…2F), suggesting that IP6K1 prevents c-Jun ubiquitylation and degradation. In line with this notion, MLN-4924, a NEDD8-activating enzyme inhibitor that reduces the neddylation and catalytic activity of CRL4 (31,32), dose-dependently increases levels of c-Jun in IP6K1-null, but not wild-type, MEFs (Fig. 2G).…”
Section: Ip6k1supporting
confidence: 66%
“…Recently, small molecules that modulate the PI3K pathway have been used for treating the ovarian tissues of human primary ovarian insufficiency patients for assisted reproduction purposes . In comparison, inhibitors of the CRL family ubiquitin E3 ligases have been used for cancer therapy (Pan et al, 2013). Our observations in these novel mouse models suggest that the key role of CRL4 DCAF1 in oocytes of growing follicles should be considered when using these new drugs in medical practice.…”
Section: Implications For Human Primary Ovarian Insufficiencymentioning
confidence: 88%
“…However, the toxicity and the development of resistance often limit its efficacy (33). Previously, a series of studies revealed that MLN4924 could be used as a sensitizer to chemotherapy: MLN4924 has been demonstrated to overcome resistance to a range of chemotherapeutics, including CDDP (20,21), carboplatin (21,34), bleomycin (35), doxorubicin (35) and etoposide (35) resistance in ovarian tumor cell lines in vitro and in vivo. MLN4924 significantly augmented the cytotoxicity of CDDP against CDDP-resistant cells in cervical carcinoma xenografts (22).…”
Section: Discussionmentioning
confidence: 99%